2020
DOI: 10.1093/infdis/jiaa486
|View full text |Cite
|
Sign up to set email alerts
|

Transient Lymphopenia and Interstitial Pneumonia With Endotheliitis in SARS-CoV-2–Infected Macaques

Abstract: Using a reliable primate model is critical for developing therapeutic advances to treat humans infected with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Here, we exposed macaques to high titres of SARS-CoV-2 via combined transmission routes. We observed acute interstitial pneumonia with endotheliitis in the lungs of all infected macaques. All macaques had a significant loss of total lymphocytes during infection, which were restored over time. These data show that SARS-CoV-2 causes a coronavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 13 publications
3
48
0
Order By: Relevance
“… 1 , 2 Studying severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in a primate model, Koo et al showed that the development of COVID-19 caused acute interstitial pneumonia with endotheliitis in the lungs. 3 These findings strengthen the implications of EC dysfunction in COVID-19. Herein, we provide a review of endothelial receptors that induce or modulate EC dysfunction in COVID-19.…”
mentioning
confidence: 54%
“… 1 , 2 Studying severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in a primate model, Koo et al showed that the development of COVID-19 caused acute interstitial pneumonia with endotheliitis in the lungs. 3 These findings strengthen the implications of EC dysfunction in COVID-19. Herein, we provide a review of endothelial receptors that induce or modulate EC dysfunction in COVID-19.…”
mentioning
confidence: 54%
“…Accordingly, macaques were challenged by multiple routes with a total dose of 2.6 × 10 7 50% tissue culture infectious doses (TCID 50 ), at 10 weeks after the last vaccination. This challenge route and dose were determined based on a model development study in which we challenged macaques that had no previous exposure to the virus [ 30 ]. Two of the three naive macaques showed elevated body temperature after viral infection, while none of the GX-19-vaccinated animals exhibited such symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…However, these data also point to potential mechanisms of disease in adults. Several studies suggest that severe COVID-19 in adults is, in part, a vascular disease [129][130][131][132] , and a MIS-C like presentation has also been observed in adults 33,133 . Although the age of patients with MIS-C (median of 8 years 40 ) likely provides a clue to MIS-C pathogenesis, it is possible that similar mechanisms of disease can occur across the age spectrum.…”
Section: Discussionmentioning
confidence: 99%